S2k Guideline for the diagnosis and treatment of mucous membrane pemphigoid. (10th November 2022) - Hofmann, Silke C.; Günther, Claudia; Böckle, Barbara C.; Didona, Dario; Ehrchen, Jan; Gaskins, Matthew; Geerling, Gerd; Gläser, Regine; Hadaschik, Eva; Hampl, Monika; Haßkamp, Pia; Jackowski, Jochen; et al.
Summary: Mucous membrane pemphigoid (MMP) is a pemphigoid disease with predominant mucous membrane involvement. It mainly affects the mucous membranes of the mouth, eyes, nose and pharynx, but also the larynx, trachea, esophagus, genital and perianal regions. The manifestation of the disease covers a wide spectrum from gingival erythema and single oral lesions to severe tracheal strictures that obstruct breathing and conjunctival scarring with marked visual impairment and, not infrequently, blindness. In addition to a clinical picture of predominant mucosal involvement, diagnosis is based on direct immunofluorescence of a peri‐lesional biopsy and serology. The main target antigen is BP180 (collagen XVII), and reactivity with laminin 332 is associated with malignancy in approximately 25 % of MMP patients. The treatment of MMP is challenging. On the one hand, due to the involvement of different mucous membranes, good interdisciplinary cooperation is required; on the other hand, due to the rarity of the disease, no randomized controlled clinical trials are available. The aim of this guideline is to present the clinical picture, including severity and scoring systems, and to give guidance for diagnosing and treating this complex disease. In MMP, interdisciplinary cooperation plays an essential role as well as the prompt diagnosis and initiation of adequate therapy in order to avoid irreversible damage to the mucous membranes with serious complications.